2018
DOI: 10.5144/0256-4947.2018.125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cochlear duct length between the Saudi and non-Saudi populations

Abstract: BACKGROUNDThere are no data on cochlear duct lengths (CDL) among Middle East populations.OBJECTIVESThe main aims of this study were to estimate the average CDL in the Saudi population and to compare it with the reported CDL in other regions/ethnic groups outside the Middle East.DESIGNRetrospective study.SETTINGTertiary otolaryngology head and neck surgery center.SUBJECTS AND METHODSTemporal bone CT scans were reviewed to determine CDL. We excluded any CT scan of an ear with a congenital inner ear anomaly or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…Our study participants were from the Saudi population, which generally shows a shorter CDL than other populations. Thus, the lower values obtained in our study are consistent with the findings reported by Alanazi et al 22 Wurfel et al 4 The mean H-value in this study was 2.71 mm (range, 2.00-3.40 mm), which was significantly shorter than those reported in few available studies that measured the height of the cochlea, such as those by Avci et a l(H-value, 4.4 mm) and Liu et al (H-value, 3.59 [0.12] mm). 10,21 In this study, we did not include age-related variables since this study aimed to evaluate the differences related to the tools we utilized and to identify the cochlear parameters that could allow more accurate estimations of CDL.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study participants were from the Saudi population, which generally shows a shorter CDL than other populations. Thus, the lower values obtained in our study are consistent with the findings reported by Alanazi et al 22 Wurfel et al 4 The mean H-value in this study was 2.71 mm (range, 2.00-3.40 mm), which was significantly shorter than those reported in few available studies that measured the height of the cochlea, such as those by Avci et a l(H-value, 4.4 mm) and Liu et al (H-value, 3.59 [0.12] mm). 10,21 In this study, we did not include age-related variables since this study aimed to evaluate the differences related to the tools we utilized and to identify the cochlear parameters that could allow more accurate estimations of CDL.…”
Section: Discussionsupporting
confidence: 94%
“…Alanazi et al conducted a study in a population with almost similar characteristics as our study population, and their results were consistent with our findings. 22 While this finding is potentially debatable, other studies have also reported longer diameters in males than in females. 4,17,23,24 However, no statistically significant difference was observed between the right and left cochlea, which indicated that there was no particular difference in morphology.…”
Section: Discussionmentioning
confidence: 96%
“…A predecessor technique to the method used with the OTOPLAN software is the technique of the spiral coefficient, introduced by Alexiades and collaborators [17]. Studies using this technique calculated similar values [15,[36][37][38]. Looking at studies using the OTOPLAN software, mean of CDL was lower (32.4 -34.0 mm; Table 2) Comparing the AID of the study of Canfarotta and collaborators [19], slightly lower values were observed in our cohort with regard to the AID (525.4° versus 578°) for FLEX28 patients, and similar values for FLEXSOFT patients (615.4° versus 619°).…”
Section: Discussionmentioning
confidence: 99%
“…The average cochlear duct length (CDL) in the Saudi population is a mean of 31.9 mm (range: 20.3–37.7 mm). 11 In our study, the CDL was 29.7 mm (range: 26–33 mm). So, the preoperative assessment indicated the use of the FORM24 to ensure complete insertion.…”
Section: Methodsmentioning
confidence: 43%